2019
DOI: 10.1186/s13059-019-1696-1
|View full text |Cite
|
Sign up to set email alerts
|

The inherited variations of a p53-responsive enhancer in 13q12.12 confer lung cancer risk by attenuating TNFRSF19 expression

Abstract: Background Inherited factors contribute to lung cancer risk, but the mechanism is not well understood. Defining the biological consequence of GWAS hits in cancers is a promising strategy to elucidate the inherited mechanisms of cancers. The tag-SNP rs753955 (A>G) in 13q12.12 is highly associated with lung cancer risk in the Chinese population. Here, we systematically investigate the biological significance and the underlying mechanism behind 13q12.12 risk locus in vitro and in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“… 50 Present evidence displayed that TNFRSF19 acted as a tumor suppressor in patients with lung cancer. 51 Although the expression details of these five members in various cancer types have been described, the combination and functions of these molecules still warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%
“… 50 Present evidence displayed that TNFRSF19 acted as a tumor suppressor in patients with lung cancer. 51 Although the expression details of these five members in various cancer types have been described, the combination and functions of these molecules still warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…acted as a tumor suppressor in patients with lung cancer. [51] Although the expression details of these five members in various cancer types have been described, the combination and functions of these molecules still warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…A recent in vivo CRISPR/Cas9-screening approach identified CEBPB binding within a p53dependent CRE required for optimal transcription of CDKN1A and initiation of senescence (22). Single nucleotide polymorphisms associated with lung cancer risk found within a p53-regulated CRE disrupt canonical transcription factor motifs, reduce p53 binding, and alter expression of TNFRSF19 (7). In this study, we identified both ATF3 and a likely member of the SP1/KLF family as co-regulatory transcription factors required for p53-dependent CRE activity.…”
Section: The Requirement For Other Transcription Factors Co-regulatinmentioning
confidence: 99%